Effect of polymorphisms in drug metabolism and transportation on plasma concentration of atorvastatin and its metabolites in patients with chronic kidney disease - Jiang, Zebin; Wu, Zemin; Liu, Ruixue; Du, Qin; Fu, Xian; Li, Min; Kuang, Yongjun; Lin, Shen; Wu, Jiaxuan; Xie, Weiji; Shi, Ganggang; Peng, Yanqiang; et al. (Frontiers in Pharmacology, 2023)
Dyslipidemia due to renal insufficiency is a common complication in patients with chronic kidney diseases (CKD), and a major risk factor for the development of cardiovascular events. Atorvastatin (AT) is mainly used in the treatment of dyslipidemia in patients with CKD. However, response to the atorvastatin varies inter-individually in clinical applications. We examined the association between polymorphisms in genes involved in drug metabolism and transport, and plasma concentrations of atorvastatin and its metabolites in kidney diseases patients. Genotypes were determined using TaqMan real time PCR in 212 CKD patients, treated with 20 mg of atorvastatin daily for 6 weeks. The steady state plasma concentrations of atorvastatin and its metabolites were quantified using ultraperformance liquid chromatography in combination with triple quadrupole mass spectrometry (UPLC−MS/MS). Univariate and multivariate analyses showed the variant in ABCC4 (rs3742106) was associated with decreased concentrations of AT and its metabolites (2-AT+2-ATL: β=-0.162, p=0.028 in the dominant model; AT+2-AT+4-AT: β=-0.212, p=0.028 in the genotype model), while patients carrying the variant allele ABCC4-rs868853 (β=0.177, p=0.011) or NR1I2-rs6785049 (β=0.123, p=0.044) had higher concentrations of 2-AT+2-ATL in plasma compared with homozygous wildtype carriers. Luciferase activity was enhanced in HepG2 cells harboring a construct expressing the rs3742106-T allele or the rs868853-G allele (p < 0.05 for each) compared with a construct expressing the rs3742106G or the rs868853-A allele. These findings suggest that two functional polymorphisms in the ABCC4 gene may affect transcriptional activity, thereby directly or indirectly affecting release of AT and its metabolites from hepatocytes into the circulation.